The occurrence and timing of delirium in acute care hospitalizations in the last year of life: A population-based retrospective cohort study. (September 2020) - Webber, Colleen; Watt, Christine L; Bush, Shirley H; Lawlor, Peter G; Talarico, Robert; Tanuseputro, Peter
Background: Delirium is a distressing neurocognitive disorder that is common among terminally ill individuals, although few studies have described its occurrence in the acute care setting among this population. Aim: To describe the prevalence of delirium in patients admitted to acute care hospitals in Ontario, Canada, in their last year of life and identify factors associated with delirium. Design: Population-based retrospective cohort study using linked health administrative data. Delirium was identified through diagnosis codes on hospitalization records. Setting/participants: Ontario decedents (1 January 2014 to 31 December 2016) admitted to an acute care hospital in their last year of life, excluding individuals age of <18 years or >105 years at admission, those not eligible for the provincial health insurance plan between their hospitalization and death dates, and non-Ontario residents. Results: Delirium was recorded as a diagnosis in 8.2% of hospitalizations. The frequency of delirium-related hospitalizations increased as death approached. Delirium prevalence was higher in patients with dementia (prevalence ratio: 1.43; 95% confidence interval: 1.36–1.50), frailty (prevalence ratio: 1.67; 95% confidence interval: 1.56–1.80), or organ failure–related cause of death (prevalence ratio: 1.23; 95% confidence interval: 1.16–1.31) and an opioid prescription (prevalence ratio: 1.17; 95% confidence interval: 1.12–1.21). Prevalence also varied by age, sex, chronic conditions, antipsychotic use, receipt of long-term care or home care, and hospitalization characteristics. Conclusion: This study described the occurrence and timing of delirium in acute care hospitals in the last year of life and identified factors associated with delirium. These findings can be used to support delirium prevention and early detection in the hospital setting.